Late-gestation protein restriction negatively impacts muscle growth and glucose regulation in steer progeny - Maresca, Sebastian; Lopez Valiente, Sebastian; Rodriguez, Alejandro Martin; Pavan, Enrique; Quintans, Graciela I.; Long, Nathan M. (Elsevier, 2019)
The objective of this study was to determine whether the amount of protein provided to cows during late gestation would affect postnatal growth and lead to changes in glucose and insulin concentrations. At 129 d of gestation, 10 mature multiparous Angus cows were stratified by body weight (BW) and body condition score (BCS) and allotted to either low protein level (LP, 6% crude protein [CP]) or high protein level (HP, 12% CP) groups. After calving, cows were managed together on improved pastures, which provided forage in excess of requirements until weaning. Male calves were maintained as a group after weaning on native range until 23 mo of age when individual steers were placed in single pens and fed a finishing diet for 84 d. The 12th rib fat thickness and longissimus muscle area were measured during finishing phase by ultrasound. Twenty days before the end of the finishing phase, steers were subjected to an intravenous glucose tolerance test. Steers were harvested and carcass characteristics collected. Cows' BW and BCS were similar at the initiation of treatment. During treatment HP dams gained 21 kg, whereas LP dams lost 7 kg (P = 0.04). Protein nutrition during late gestation did not influence calf birth weight, BW at weaning, adjusted 205 d BW, or average daily gain during lactation (P > 0.10). Longissimus muscle area measure by ultrasound was greater (P = 0.02) in HP steers at the beginning and end of finishing phase. Fat thickness of the 12th rib was not different (P > 0.10) between treatments. Glucose concentration after intravenous administration decreased (P = 0.002) in LP compared with HP steers. Peak of serum insulin concentration was greater (P = 0.04) and serum insulin concentration tended to decrease (P = 0.08) more rapidly in LP compared with HP steers after glucose infusion. At harvest, hot carcass weight was similar between treatments, but dressing percentage was increased (P = 0.05) in HP compared with LP steers. These data demonstrate that a lower protein nutrition level of dams during late gestation affect carcass characteristics and alter glucose regulation enhancing insulin secretion in steer progeny.